2011
DOI: 10.1021/es200057g
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Catalytic Microwave Method To Damage Microcystis aeruginosa with FeCl3-Loaded Active Carbon

Abstract: In recent years, effective methods for cyanobacterial blooms treatment have been an important issue. In this study, we demonstrated a rapid catalytic microwave method to deal with Microcystis aeruginosa with FeCl(3)-loaded active carbon. Microcystis aeruginosa damage process was monitored by measuring optical density, chlorophyll-a content, superoxide dismutase activity, l-glutathione content, and turbidity of the treated Microcystis aeruginosa suspension. It was found that this method could quickly and effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 37 publications
3
19
0
Order By: Relevance
“…These excited electrons could transfer from AC to Fe@Fe 2 O 3 because of the excellent conductivity of the latter. Similar phenomenon was observed in our previous work, in which we found that MW irradiation could induce the separation of the electron/hole pairs in AC via the so-called charge transfer-induced doping effect, which could realize electrons transferring from AC to Fe 3+ ions [21]. On the basis of the previous studies and the above experimental results, we proposed a possible mechanism for the reactive oxygen species generation via molecular oxygen activation over Fe@Fe 2 O 3 /AC under MW irradiation (Fig.…”
Section: The Possible Mechanism Of Reactive Oxygen Species Generationsupporting
confidence: 90%
See 4 more Smart Citations
“…These excited electrons could transfer from AC to Fe@Fe 2 O 3 because of the excellent conductivity of the latter. Similar phenomenon was observed in our previous work, in which we found that MW irradiation could induce the separation of the electron/hole pairs in AC via the so-called charge transfer-induced doping effect, which could realize electrons transferring from AC to Fe 3+ ions [21]. On the basis of the previous studies and the above experimental results, we proposed a possible mechanism for the reactive oxygen species generation via molecular oxygen activation over Fe@Fe 2 O 3 /AC under MW irradiation (Fig.…”
Section: The Possible Mechanism Of Reactive Oxygen Species Generationsupporting
confidence: 90%
“…Coal-based columnar activated carbon was washed with de-ionized water for several times and then immersed in 8-10 wt% hydrochloric acid for 18 h. The acid treated activated carbon was then treated with boiling water for 2 h and washed with de-ionized water until the pH reached 5-6. Finally, the pretreated AC was dried in an oven at 105 • C for 8 h for use [21][22][23][24]. For the loading of Fe@Fe 2 O 3 core-shell nanowires, the pretreated AC was first soaked in ferric chloride solution (FeCl 3 , 0.1 M) under stirring for 3 h for ferric iron absorption.…”
Section: Preparation Of the Fe@fe 2 O 3 /Ac Catalystmentioning
confidence: 99%
See 3 more Smart Citations